The Slippery Simultaneities of Remembering and Forgetting: Memory, Autobiographical Narrative, and the Case of Nathalie Sarraute's Enfance. (3rd May 2016) - Lewkowich, David
ABSTRACT: Considering the question of how to represent the concealments and disintegrations of forgetting, this article theorizes the inextricable play of memory in Nathalie Sarraute's Enfance, whose fragmented descriptions of childhood experience work to emphasize the problems of representation in relation to narrative acts of autobiographical remembering.